Leaching-induced alterations in the geotechnical and microstructural attributes of clayey gypseous soils - Hassan Al-Riahi S.M.; Irfah Mohd Pauzi N.; Fattah M.Y.; Ali Abbas H. (Ain Shams University, 2025)
In this paper, an attempt has been made to investigate the impacts of leaching on the geotechnical and microstructural properties of clayey gypseous soils at various percentages of gypsum; 20 %, 40 %, and 60 %, and their respective densities. In this respect, the work delves into the interaction of the properties based on the following experiments: oedometer permeability leaching and modified permeability leaching tests for investigating the effects of gypsum content, density, and leachate on significant soil properties such as compressibility, permeability, and Total dissolved solids (TDS). Scanning electron microscopy (SEM) and Energy dispersive spectroscopy (EDS) used for microstructural analysis reveal how the soil fabric and dissolution patterns change during leaching. The conclusions derived from the results of the study state that with an increase in the content of gypsum in soil, it increases the porosity and permeability of the soil and at the same time decreases the plasticity. The soils which were denser showed lesser leaching strain due to reduced permeability. It can be ascertained that the modified leaching test is a more realistic and accurate method in comparison to the oedometer test. Results from microstructural observations hence bring out important changes in the soil fabric after leaching: increases in voids and cavities responsible for the change of soil stability and engineering properties. This research allows a good contribution to understanding and the management of gypseous soil behavior in geotechnical engineering projects and provides new lines of future investigation for the long-term performance and stabilization technique of effectiveness. ? 2024